Examining the Efficacy of Time Scarcity Marketing Promotions in Online Retail - Hmurovic, Jillian; Lamberton, Cait; Goldsmith, Kelly (Journal of Marketing Research, 2023)
Time scarcity promotions (e.g., “40% off for a limited time”) are mainstays of online retail marketing. Although positive effects of time scarcity promotions on consumer interest have been evidenced in the brick-and-mortar world, should retailers expect similarly robust effects online? The present research suggests the answer may be no. First, the authors report meta-analytic and experimental results suggesting that previously identified positive effects of time scarcity promotions observed offline may not emerge in online shopping contexts. Then, consistent with the prediction that online time scarcity promotions activate more persuasion knowledge than identical control promotions, the authors detail findings suggesting that providing retailer-exogeneous justifications for online time scarcity promotions’ time restriction (e.g., consumers’ birthdays, seasonal changes) can increase the potential of observing positive effects on consumer interest online. Further, results suggest that the positive effects of including exogenous time justification may be more likely when less time remains until the online promotion’s expiration. However, results stop short of suggesting that online time scarcity promotions will consistently yield superior outcomes compared with identical online control promotions. Therefore, the authors highlight the continued need for careful managerial use as well as further research examining the optimal translation of offline tactics to online retail.